Investigation on removal mechanism in catalytic aided electrical discharge machining of polycrystalline diamond - Ahmad, Muhammad Ariff Haikal (2019)
Electrical Discharge Machining (EDM) is a non-contact machining process that has become famous in machining of Polycrystalline Diamond (PCD). PCD is typically used as a cutting tool for aerospace and automotive industries as the material has high hardness (~80GPa) and strength (~60Gpa). However, low electrical conductivity (~10−13 S/m) and high melting temperature (3400oC) of PCD has caused slower EDM process. This investigation is purposely designed to investigate the EDM performance, machined surface and erosion mechanism of PCD in the influence of different types of electrode which are Copper-Nickel (Cu-Ni) and Copper (Cu) in roughing and finishing condition. Two levels of full factorial with eight center points and two replication technique was used to study the influence of main and interaction effects of the machining parameter. Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), Raman spectroscopy and oscilloscope were used for the mechanism analysis. In roughing condition, though 65% slower material removal rate (MRR) was obtained, Cu-Ni electrode produced better electrode wear ratio (EWR) of up to 500% in comparison to ordinary electrode. This is because lower electrical and thermal conductivity of Cu-Ni electrode produces high percentages of arching (immature discharge) which is inadequate to produce better MRR compared to Cu electrode. Meanwhile, different phenomena occurred in finishing condition in which the newly proposed electrode of Cu-Ni gave positive impact to the MRR. It is interesting as the Cu-Ni produced 14% higher MRR than the Cu electrode with its higher short circuiting rate. Cu-Ni also recorded the lowest surface roughness (Ra) value with 16% better than the best Ra produced by Cu electrode. These phenomena occurred due to the high interaction between the catalyst materials of nickel and diamond during short circuiting as supported by the chemical analysis. Due to the EDX analysis, the migration of catalyst materials into PCD was significant in finishing condition and it indicated that the catalyst electrode accelerated the graphitization process of PCD.